Publicaciones (Casos clínicos y tesis) en la facultad de odontología de la universidad San Marcos: 1995-2002 - Moromi Nakata, Hilda (2002)
With the purpose of show the tendency of the publications production: clinic cases and thesis, developed in the Odontology Faculty of the San Marcos University, it shows an analytic study of the tendency of that registered publications between the 1995 and 2002. Was found: 1) between 1995 and 2002, it has been produced 135 publications, in which 28, 1 % were clinic cases, and 71,9 % were thesis; 2) in the period of time studied, there was a increasing tendency, reaching the high level in 1999 (35,6 %), to then suffer a decrease to levels below 10 %; 3) The biggest production happened in areas that belong to the Academic Department Of Medicine and Surgery (50,4 %), followed by the Department of Rehabilitate Estomatology (23,7 %); 4) In the areas of the Departments of Basic Sciences, Rehabilitate Estomatology and Biosocial, there was a lack of clinic cases; and 5) the 61,5 % were produced by male students and 58,5 % by female students.